Study of mass accretion of fluids flow near the horizon of charged acoustic black hole - Puja Mukherjee; Ujjal Debnath; Pameli Saha (European Physical Journal C: Particles and Fields)
Abstract In the astrophysical universe, the falling matter accretion around the black hole is becoming an engrossing chapter. Our present manuscript reveals the matter accretion onto the acoustic-charged black hole in the background of Gross–Pitaevskii theory. This type of black hole is popular to several researchers. Following Hamiltonian dynamics, we go through the accretion process to face the cosmological mechanism. Depending on the tuning parameter $$ξ $$ ξ of this black hole, we formulate sonic points to have a physical analysis of the speed of sound at sonic points. Undergoing the isothermal test fluids, we generate field equations at sonic points for our proposed model. Then we observe the accretion flow of the distinctive fluids around the acoustic-charged black hole with the variation of the tuning parameter. The most fascinating part of this work is to look for an analysis of the rate of flow of mass accretion of the different kinds of fluid onto our proposed black hole at sonic points with a graphical analysis. By investigating the accretion rate of these fluids, we seek stable and reliable results to check the compactness with the observational data.